KEMAMPUAN REPRESENTASI SISWA DENGAN PENERAPAN MODELING INSTRUCTION PADA PEMBELAJARAN FISIKA SMA - Rika Triandani Rika Triandani; Mitri Irianti Mitri Irianti; Muhammad Nor Muhammad Nor (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: the aim of this research is to describe students representation ability in applaying Modeling Instruction on Dynamic Electicity at SMAN 5 Pekanbaru. The expected benefits of this research is to train the student in using such representation (verbal, mathematics, graphs and pictorial), in order to increase student representation ability. This research was conducted at SMAN 5 Pekanbaru in X8 class totaling 39 students. The design of the research is Pre-experimental design formone shot case study. Through applying Modeling Instruction, student trained to serve representation to such kind of representation: verbal representation, mathematics representation, graphs representations, pictorial representation. From the research, based of aspect representation ability; formulate information from a representation, forming a new representation, the consistency of representation and solve problems using the representation obtained the ability of student representation by implementing of Modeling Instruction obtained the criteria of representation ability categorized medium level with an average score 76,50. therefore in teaching physics, by using Modeling Instruction could train the first year student representation ability on dynamic electric material at SMAN 5 Pekanbaru.Kata Kunci: Modeling Instruction, representation ability, Dynamic electicity